2012
DOI: 10.1158/0008-5472.can-11-3208
|View full text |Cite
|
Sign up to set email alerts
|

Densely Granulated Murine NK Cells Eradicate Large Solid Tumors

Abstract: NK cells inhibit early stages of tumor formation, recurrence and metastasis. Here we show that NK cells can also eradicate large solid tumors. Eradication depended on the massive infiltration of proliferating NK cells due to IL15 released and presented by the cancer cells in the tumor microenvironment. Infiltrating NK cells had the striking morphological feature of being densely loaded with PAS-positive, diastase-resistant granules, resembling uterine NK cells. Perforin-mediated killing by these densely granul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 47 publications
(42 reference statements)
3
44
0
Order By: Relevance
“…Co-expression of IL-15Ra by the tumor cells was needed for the efficient induction of the densely granulated NK effector cells in the tumor microenvironment. Moreover, the regression of the IL-15-secreting tumors did not stop the growth of contralateral non-IL-15-secreting control tumors, suggesting that the effect of IL-15 was largely restricted to the local microenvironment of the IL-15-secreting tumor (54). On the other hand, in another mouse model, it was shown that the hypoxic conditions in the tumor induced the upregulation of 4-1BB on tumorinfiltrating lymphocytes (TIL), which could be selectively activated by local, that is, intratumoral application of 4-1BB-specific monoclonal antibodies, promoting the development of an effective antitumor response without causing liver side effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Co-expression of IL-15Ra by the tumor cells was needed for the efficient induction of the densely granulated NK effector cells in the tumor microenvironment. Moreover, the regression of the IL-15-secreting tumors did not stop the growth of contralateral non-IL-15-secreting control tumors, suggesting that the effect of IL-15 was largely restricted to the local microenvironment of the IL-15-secreting tumor (54). On the other hand, in another mouse model, it was shown that the hypoxic conditions in the tumor induced the upregulation of 4-1BB on tumorinfiltrating lymphocytes (TIL), which could be selectively activated by local, that is, intratumoral application of 4-1BB-specific monoclonal antibodies, promoting the development of an effective antitumor response without causing liver side effects.…”
Section: Discussionmentioning
confidence: 98%
“…For example, it was shown in mouse models that na€ ve CD8 þ T cells can infiltrate tumors and become activated and differentiated into functional effector cells in situ (53). Studies in mice provided evidence that localized activity of IL-15 and 4-1BB in the tumor microenvironment was relevant for the respective antitumor response (54,55). Thus, in a Rag1…”
Section: Discussionmentioning
confidence: 99%
“…In a separate mouse study, in which solid tumors were composed of fibrosarcoma cells engineered to secrete IL-15, NK cells were able to eradicate the large solid tumors (11). Though these findings clearly show the potential of IL-15 in driving solid tumor killing, IL-15 was restricted to the tumor microenvironment (TME), and was not increased systemically, so it is hard to evaluate whether the antitumor function was mediated by NK cells residing in the TME long term or by newly infiltrated NK cells being primed by the IL-15 short term.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-15 (IL-15) was also included in the mentioned studies, since it is important in regulating NK cell function and survival, 27,28 and for efficient antitumor NK cell activity. 29 Indeed, we reported that both, IL-12 and IL-15 activated PKC-u in NK cells, with IL-15 being more potent at inducing PKC-u phosphorylation. More importantly, in a mixed splenocyte culture stimulated ex vivo with poly I:C, neutralizing antibodies against IL-15 substantially reduced NK cell PKC-u phosphorylation, whereas IL-12 antibody blockade was ineffective.…”
Section: Introductionmentioning
confidence: 90%